Dry season ecology of Anopheles gambiae complex mosquitoes in The Gambia - Jawara, Musa (BioMed Central, 2008)
BACKGROUND: Malaria in The Gambia is highly seasonal, with transmission occurring as Anopheles gambiae s.l. populations expand during and immediately after a single annual rainy season that lasts from June to October. There has been very limited investigation of the ecology of vectors during the dry season, when numbers are very limited and distributions may be restricted. METHODS: Weekly adult mosquito collections (pyrethrum spray, light trap, and search collections from rooms, as well as light trap collections from animal shelters, abandoned wells and grain stores), and artificial sentinel breeding site surveys were performed in four villages near the upper tidal and partially saline part of the Gambia River in the last four months of an annual dry season (March to June). Mosquito species were identified by morphological and DNA analysis, and ELISA assays were performed to test for Plasmodium falciparum sporozoites and human blood meal components. RESULTS: Adults of An. gambiae s.l. were collected throughout the period, numbers increasing towards the end of the dry season when humidity was increasing. Adult collections were dominated by An. melas (86%), with An. gambiae s.s. (10%) and An. arabiensis (3%) also present throughout. Most females collected in room search and spray collections contained blood meals, but most from light traps were unfed. None of the females tested (n = 1709) contained sporozoites. Larvae (mostly An. gambiae s.s.) were recovered from artificial sentinel breeding sites in the two villages that had freshwater pools. These two villages had the highest proportions of An. gambiae s.s. adults, and experienced the most substantial increase in proportions of An. gambiae s.s. after the onset of rains. CONCLUSION: During the dry season population minimum, An. melas was the predominant vector species, but differences among villages in availability of fresh-water breeding sites correlate with egg laying activity and relative numbers of An. gambiae s.s. adults, and with the increase in this species immediately after the beginning of the rains. Local variation in dry season vector persistence is thus likely to influence spatial heterogeneity of transmission intensity in the early part of the rainy season.